2017
DOI: 10.2308/bria-51756
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Time Pressure on Belief Revision in Accounting: A Review of Relevant Literature within a Pressure-Arousal-Effort-Performance Framework

Abstract: This study advances several propositions about the effects of time pressure on individuals' belief revisions within a pressure-arousal-effort-performance framework. There is a significant body of research that documents the importance of both time pressure and order effects in an accounting environment. However, prior research has not investigated how the order of information affects individuals' belief revision processes under varying levels of time pressure, even though the inclusion of a time pressure varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 102 publications
3
5
0
3
Order By: Relevance
“…Therefore, it is recognized that time pressure could be able to influence the auditors' job performance in Malaysia. This finding is consistent with the findings of previous studies by Pietsch and Messier (2017) as well as Svanberg and Ohman (2013) who also found the positive influence of time pressure on auditor performance. On the other hand, this finding is contradict with study conducted by Sacramento et al (2013) and Wijaya and Yulyona (2017) which stated that time pressure did not influence the job performance.…”
Section: Discussion Of Findingssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, it is recognized that time pressure could be able to influence the auditors' job performance in Malaysia. This finding is consistent with the findings of previous studies by Pietsch and Messier (2017) as well as Svanberg and Ohman (2013) who also found the positive influence of time pressure on auditor performance. On the other hand, this finding is contradict with study conducted by Sacramento et al (2013) and Wijaya and Yulyona (2017) which stated that time pressure did not influence the job performance.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Thus, the second hypothesis (H2) was supported. The result are consistent with the finding of previous studies by Pietsch and Messier (2017) as well as Svanberg and Ohman (2013) who also found the positive influence of time pressure on auditor performance.…”
Section: Multicollinearity Testsupporting
confidence: 93%
See 1 more Smart Citation
“…However, work overload and time pressures, far from improving the performance of the professionals, endanger the quality of the work. The duality of effects, positive and negative, that the scientific literature has identified in relation to work overload is explained with the approach of the Arousal Theory, for which the relationship between stress and performance is U-shaped inverted, as pointed out in Reference [ 33 ]. As Reference [ 34 ] points out, the elimination of stress in accounting is a utopia, given the characteristics of this type of activity—for instance, seasonality linked to compliance with trade regulations, tight deadlines (so that customers can give timely information to the markets), tight time and monetary budgets by the increased competitiveness of the sector, the complexity of some decisions of the audit, manipulation of information by customers.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…For example, deadlines can be shortened, or data can be passed on later. The importance and effects of time pressure have been examined widely in the literature (Kelly et al, 2011;Lambert et al, 2017;Pietsch & Messier, 2017;Spilker, 1995;Wegier & Spaniol, 2015).…”
Section: The Impact Of Time Pressure On Algorithm Aversionmentioning
confidence: 99%